Hubungan Tingkat Pendidikan dan Pengetahuan Ibu dengan Kejadian ISPA pada Balita di Kepulauan Sangkarrang - Ernawati; Wa Mina La Isa (ProHealth Journal, 2021)
The under-five mortality rate due to ARI can be caused by low levels of education and lack of parental knowledge about ARI itself. In general, parents underestimate cough and cold as not dangerous because usually this disease can affect children repeatedly and heal by itself. However, they do not understand that this disease can develop into a serious disease if it is not treated and treated immediately, especially when the child's immune system decreases. This research is a correlational study using a cross sectional approach, the sample size is 82 mothers who have toddlers in the Sangkarang Islands. Data collection through interviews and direct observation in the field on September 15-23 2019. To see the relationship between education level and mother's knowledge with the incidence of ARI using Chi Square statistical analysis. The results of this educational level study obtained a value of p = 0.000 with an error level of α = 0.05. In conclusion, there is a relationship between education level and the incidence of ARI in toddlers in the Sangkarrang Islands. And the results of this mother's knowledge research obtained a value of p = 0.000 with an error level of α = 0.05. In conclusion, there is a relationship between mother's knowledge and the incidence of Acute Respiratory Infection (ARI) in Toddlers in the Sangkarrang Islands.